Accelerated Regeneration of ATP Level after Irradiation in Human Skin Fibroblasts by Coenzyme Q10. (18th April 2016) - Schniertshauer, Daniel; Müller, Sonja; Mayr, Tobias; Sonntag, Tanja; Gebhard, Daniel; Bergemann, Jörg
Abstract: Human skin is exposed to a number of harmful agents of which the ultraviolet (UV) component of solar radiation is most important. UV‐induced damages include direct DNA lesions as well as oxidative damage in DNA, proteins and lipids caused by reactive oxygen species (ROS). Being the main site of ROS generation in the cell, mitochondria are particularly affected by photostress. The resulting mitochondrial dysfunction may have negative effects on many essential cellular processes. To counteract these effects, coenzyme Q10 (CoQ10 ) is used as a potent therapeutic in a number of diseases. We analyzed the mitochondrial respiration profile, the mitochondrial membrane potential and cellular ATP level in skin fibroblasts after irradiation. We observed an accelerated regeneration of cellular ATP level, a decrease in mitochondrial dysfunction as well as a preservation of the mitochondrial membrane potential after irradiation in human skin fibroblasts by treatment with CoQ10 . We conclude that the faster regeneration of the ATP level was achieved by a preservation of mitochondrial function by the addition of CoQ10 and that the protective effect of CoQ10 is primarily mediated via its antioxidative function. We suggest also that it might be further dependent on a stimulation of DNA repair enzymes by CoQ10 . Abstract : Being the main site of ROS generation in the cell, mitochondria are particularly affected by photostress. The resulting mitochondrial dysfunction may have negative effects on many essential cellular processes. To counteract these effects, CoQ10 is used as a therapeutic in a number of diseases. We observed that CoQ10 is able to preserve the mitochondrial membrane potential after SSL‐UVA irradiation (d, e ), decrease the level of mitochondrial dysfunction (a, b ) and lead therefore to a more rapid regeneration of the cellular ATP levels in human fibroblasts (c ). We conclude that the protective effect of CoQ10 is primarily mediated via its antioxidative function.